Methods of Creating a Personal Bibliography of a Composer’s Opus - Zoran Krstulović (Knjižnica)
ABSTRACT The article deals with different approaches to creating a personal bibliography of a composer’s opus. Methods of bibliographic descriptions of musical works in general bibliographies were examined with special emphasis on a thorough examination of methods of creating personal bibliographies of Slovenian composers from the beginning to the present. Special attention was given to the bibliographies of Emil Adamič, the first one dating in 1937 and the new one from the year 2004, and the bibliography of Vasilij Mirk. Three different approaches were identified. Bibliographic records are arranged according to the form of musical works, performers or types of music, furthermore, the records are arranged either alphabetically by the title or chronologically by the year of creation. Methods of creating a bibliography of a composer’s opus are presented for the first time resulting in guidelines for the organisation of bibliographic descriptions that will help bibliographers in their future endeavours.